Answer:
40 years old
Explanation:
Define the variables:
- Let r be Ryan's age (in years).
- Let s be Stacy's age (in years).
Given Ryan is 93 years younger than Stacy:
⇒ r = s - 93
Given 9 years ago, Stacy's age was 4 times Ryan's age:
⇒ 4(r - 9) = (s - 9)
Substitute the first equation into the second equation and solve for s:
⇒ 4(s - 93 - 9) = (s - 9)
⇒ 4(s - 102) = s - 9
⇒ 4s - 408 = s - 9
⇒ 3s = 399
⇒ s = 133
Substitute the found value of s into the second equation and solve for r:
⇒ r = 133 - 93
⇒ r = 40
Therefore, Ryan is 40 years old now.